Parental love language and its relationship with early childhood character formation - Astuti, Kartika; Aryani, Nini; Rahayu, Swandra (Thufuli : Jurnal Ilmiah Pendidikan Islam Anak Usia Dini, 2026)
Drawing on Gary Chapman’s (1995) five-dimensional framework words of affirmation, quality time, receiving gifts, acts of service, and physical touch, this research explored how parents’ modes of expressing affection relate to measurable aspects of their children’s character. Child character was assessed across four indicators: honesty, discipline, tolerance, and independence, anchored in Lickona’s (1991) character education framework. A quantitative correlational design was adopted, with data gathered from 30 parents of children aged 4–5 years selected through purposive sampling from a population of 89 respondents. Data collection employed a four-point Likert scale questionnaire with established validity and reliability (α = 0.812). Pearson Product Moment correlation was applied after confirming the assumptions of normality and linearity. Results revealed a positive and statistically significant relationship between parental love language and child character (r = 0.740; p < 0.01), classified as a strong correlation. The coefficient of determination indicated that love language accounted for 54.76% of the variance in child character scores, while the remaining 45.24% was attributable to external factors. Among the five dimensions, words of affirmation emerged as the most influential predictor. These findings highlight that emotionally attuned, language-rich interactions between parents and children constitute a foundational pillar of early childhood character development.